2011
DOI: 10.1007/s11062-011-9184-6
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of High-Frequency EEG Rhythms under Conditions of the Activation Reaction: Dependence on Psychological Characteristics of Personality

Abstract: In a group of 118 adults of both sexes, we studied modulation of high-frequency EEG rhythms (β and γ components) under conditions of EEG activation related to opening of the eyes. Typical changes in the α rhythm (significant depression in the overwhelming majority of the tested subjects) was accompanied by different (in direction and intensity) shifts of the spectral powers (SPs) of the β and γ components in different subjects. The power of the β1 subcomponent under conditions of the activation reaction increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…threat detection, escape/avoidance) states. Supporting this hypothesis, previous studies showed that eye state modulated the relationship between high frequency and low frequency EEG rhythms and the neuroticism trait from the Eysenck Personality Questionnaire (Konareva, 2011a(Konareva, , 2011b. Furthermore, fMRI studies have shown that blood oxygen-level dependent (BOLD) signals of key regions within the defensive system, such as the hippocampus and amygdala, are modulated by EO and EC conditions (Ben-Simon et al, 2008;Jao et al, 2013;Liu et al, 2013;Wiesmann et al, 2006).…”
Section: Introductionmentioning
confidence: 90%
“…threat detection, escape/avoidance) states. Supporting this hypothesis, previous studies showed that eye state modulated the relationship between high frequency and low frequency EEG rhythms and the neuroticism trait from the Eysenck Personality Questionnaire (Konareva, 2011a(Konareva, , 2011b. Furthermore, fMRI studies have shown that blood oxygen-level dependent (BOLD) signals of key regions within the defensive system, such as the hippocampus and amygdala, are modulated by EO and EC conditions (Ben-Simon et al, 2008;Jao et al, 2013;Liu et al, 2013;Wiesmann et al, 2006).…”
Section: Introductionmentioning
confidence: 90%
“…Moreover, a previous study investigating differences in FC between individuals with generalized anxiety disorder and controls showed that there were some differences that were irrespective of eye status, but also that some differences only manifested during a specific eye condition (W. . Notably, a previous EEG study showed how eye state modulated the relationship between frequency bands and diverse personality factors, including neuroticism (Konareva, 2011). Despite this evidence, no study has investigated whether or not eye state modulates the manifestation of personality factors in fMRI resting state paradigms.…”
Section: Introductionmentioning
confidence: 99%